The Middle Cambrian fossil Pikaia and the evolution of chordate swimming - Lacalli, Thurston (BioMed Central, 2012)
Conway Morris and Caron (2012) have recently published an account of virtually all the available information on Pikaia gracilens, a well-known Cambrian fossil and supposed basal chordate, and propose on this basis some new ideas about Pikaia’s anatomy and evolutionary significance. Chief among its chordate-like features are the putative myomeres, a regular series of vertical bands that extends the length of the body. These differ from the myomeres of living chordates in that boundaries between them (the myosepta) are gently curved, with minimal overlap, whereas amphioxus and vertebrates have strongly overlapping V- and W-shaped myomeres. The implication, on biomechanical grounds, is that myomeres in Pikaia exerted much less tension on the myosepta, so the animal would have been incapable of swimming as rapidly as living chordates operating in the fast-twitch mode used for escape and attack. Pikaia either lacked the fast-twitch fibers necessary for such speeds, having instead only slow-twitch fibers, or it had an ancestral fiber type with functional capabilities more like modern slow fibers than fast ones. The first option is supported by the sequence of development in zebrafish, where both myoseptum formation and fast fiber deployment show a dependence on slow fibers, which develop first. For Pikaia, the absence of fast fibers has both behavioral and anatomical implications, which are discussed. Among the latter is the possibility that a notochord may not have been needed as a primary stiffening device if other structures (for example, the dorsal organ) could perform that role.